Does Warm-Up Have a Beneficial Effect on 100-m Freestyle? - Neiva, Henrique (2014)
To investigate the effect of warm-up on 100-m swimming performance. Twenty competitive swimmers (with a training frequency of 8.0 ± 1.0 sessions/wk) performed 2 maximal 100-m freestyle trials on separate days, with and without prior warm-up, in a counterbalanced and randomized design. The warm-up distance totaled 1000 m and replicated the swimmers' usual precompetition warm-up strategy. Performance (time), physiological (capillary blood lactate concentrations), psychophysiological (perceived exertion), and biomechanical variables (distance per stroke, stroke frequency, and stroke index) were assessed on both trials. Performance in the 100-m was fastest in the warm-up condition (67.15 ± 5.60 vs 68.10 ± 5.14 s; P = .01), although 3 swimmers swam faster without warm-up. Critical to this was the 1st 50-m lap (32.10 ± 2.59 vs 32.78 ± 2.33 s; P < .01), where the swimmers presented higher distance per stroke (2.06 ± 0.19 vs. 1.98 ± 0.16 m; P = .04) and swimming efficiency compared with the no-warm-up condition (stroke index 3.46 ± 0.53 vs 3.14 ± 0.44 m2 · c1 · s1; P < .01). Notwithstanding this better stroke-kinematic pattern, blood lactate concentrations and perceived exertion were similar between trials. These results suggest that swimmers' usual warm-up routines lead to faster 100-m freestyle swimming performance, a factor that appears to be related to better swimming efficiency in the 1st lap of the race. This study highlights the importance of performing swimming drills (for higher distance per stroke) before a maximal 100-m freestyle effort in similar groups of swimmers.